SISTEM PENDIDIKAN ISLAM STUDI PERBANDINGAN DI ACEH DAN NEGERI KELANTAN: SUATU ANALISIS TERHADAP PEMIKIRAN SYED MUHAMMAD NAQUIB AL-ATTAS - Dicky Wirianto, Dicky Wirianto (Yayasan Darul Hasanah Aceh, 2025)
The Islamic education system in Aceh and Kelantan has characteristics that reflect a distinctive historical, cultural, and Islamic heritage. This paper aims to analyze the comparison of the Islamic education system in these two regions by referring to the thoughts of Syed Muhammad Naquib al-Attas, a prominent Islamic intellectual figure. Al-Attas is known for his concepts of education that emphasize the development of character, an integral understanding of knowledge, and the formation of individuals who are balanced in spiritual, intellectual, and social aspects. One of the educational terminologies he offers is the concept of At-Ta'dib. In Aceh, the Islamic education system is influenced by the dayah tradition, which emphasizes the teaching of classical Islamic texts and religious development, while in Kelantan, Islamic education is more structured in a curriculum that includes the integration of religious and general knowledge. Through an analysis of Al-Attas's thinking, it can be seen that both have the potential to develop education that focuses not only on religious teaching, but also on character building in accordance with deep Islamic principles. This paper provides insight into the importance of integrating religious knowledge and worldly knowledge to produce a generation that excels in spiritual and intellectual aspects.